Elaboração de proposta de valor em startups: uma teoria fundamentada na trajetória de empreendedores em cleantechs brasileiras - Susteras, Guilherme Luiz (2022)
The objective of any new business is to create value – even though the share of value appropriation by each stakeholder can vary considerably, either due to the entrepreneur's deliberate decision or due to market conditions. The study of the dynamics of value creation and appropriation by new companies has received great attention both in the fields of Strategy and Entrepreneurship. The entrepreneur's strategic role should be to seek the maximization of value creation in their new business by increasing customers' willingness to pay, which is linked to customers' expectations on how the company's Value Proposition will satisfy their needs, a topic widely studied in field of Marketing. In this sense, the Value Proposition is perceived as a critical success factor for innovative companies in emerging markets. In this context, the theme, which is at the intersection of the research fields of Strategy, Entrepreneurship and Marketing, lacks studies that investigate the design of Value Proposition by innovative companies and, thus, the objective of this work is to understand how entrepreneurs develop the Value Proposition of their companies. The subjects of this study were Brazilian companies that offer products and services based on clean technologies (cleantechs). The philosophical perspective adopted was social constructivism, with a qualitative research strategy and a grounded theory methodological approach, with data collection through semi-structured interviews with entrepreneurs who are owners of cleantech startups. The research resulted in seven theoretical propositions, which were organized schematically into a theoretical model that explains how cleantech founders design their value propositions. As such, this work brings as theoretical contribution an empirical model of the dynamics of the elaboration of value propositions during the design phase of cleantech startups’ business models and, from a practitioners’ point of view, it will support entrepreneurs as they design their business models, insofar as it clarifies the process of elaboration and application of value propositions by innovative startups. It is expected that the model may instigate the reflection by startup founders, reinforcing the importance of duly considering the motivation for creating a new business and bringing realistic elements for expectations management during the business creation phase.